Implementation of Horizontal Infiltration Pipes System for Sustainable Drainage at Demakan Village Office, Banyubiru, Semarang Regency - Lindawati; Lestari, Fitria Maya; Herdiarti, Etika; Rivani, Yonikha; Masvika, Hendra (Jurnal Pengabdian KOLABORATIF, 2026)
The primary issue in Demakan Village, Banyubiru, Semarang Regency, is the high volume of rainwater runoff that frequently causes puddles in public areas. This community service aims to implement Horizontal Infiltration Pipe (HIP) technology as an eco-friendly drainage solution. The implementation method consisted of coordination and socialization with village officials and residents, site surveys, system design, and installation of a perforated horizontal infiltration pipe network at the Demakan Village Office on 15 November 2025. The implementation resulted in the successful establishment of a functional HIP system that reduced localized ponding around the office area, facilitated rainwater infiltration into the surrounding soil, and served as a practical demonstration of sustainable drainage technology for the community. The activity also strengthened the understanding of village stakeholders regarding environmentally sound drainage management and groundwater conservation. In conclusion, the HIP system proved to be a feasible alternative to conventional vertical infiltration structures, particularly in areas with limited space and specific soil conditions. The installed system can serve as a pilot model for sustainable drainage management in Banyubiru, while routine maintenance and periodic monitoring are recommended to ensure long-term system performance and support groundwater recharge.